2017
DOI: 10.3389/fpsyg.2017.01194
|View full text |Cite
|
Sign up to set email alerts
|

Finding the SNARC Instead of Hunting It: A 20∗20 Monte Carlo Investigation

Abstract: The Spatial Numerical Association of Response Codes (SNARC) effect describes a stimulus-response association of left with small magnitude and right with large magnitude. Usually, it is estimated by means of regression slopes, where the independent variable only has a limited number of levels. Inspection of the literature reveals that it is not difficult to detect a SNARC effect within a group, but it has been quite unusual to find group differences. Is the SNARC effect as it is usually estimated using regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…When more trials are included for averaging, the errors associated with the single measurements tend to cancel each other out more accurately 16 . In the case of the SNARC effect, increasing the number of repetitions of each number per block up to 20 or 30 seems a reasonable solution, because the duration of the task does not change dramatically and still can be well below 20 minutes (for simulations, see Cipora & Wood, 2017). In the presented analyses, reliability is at least at an acceptable level (≥ .66) in all studies using 20 and more repetitions 17 .…”
Section: Improving Snarc Effect Reliability and Precisionmentioning
confidence: 77%
“…When more trials are included for averaging, the errors associated with the single measurements tend to cancel each other out more accurately 16 . In the case of the SNARC effect, increasing the number of repetitions of each number per block up to 20 or 30 seems a reasonable solution, because the duration of the task does not change dramatically and still can be well below 20 minutes (for simulations, see Cipora & Wood, 2017). In the presented analyses, reliability is at least at an acceptable level (≥ .66) in all studies using 20 and more repetitions 17 .…”
Section: Improving Snarc Effect Reliability and Precisionmentioning
confidence: 77%
“…Unlike other reports, we did not observe significantly negative SNARC effects for numbers (and for weekdays) with the 1–5 range without any stimulation (e.g., Dehaene et al, 1993 ; Fias et al, 1996 ). It should be acknowledged as well that internal consistency and reliability of the SNARC effect can be medium to low (Cipora and Wood, 2017 , for simulations; Cipora and Nuerk, 2013 ; Viarouge et al, 2014 ; Georges et al, 2016 ; for estimates of reliability from 0.27 to 0.70), which may also influence differences between two tDCS conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies reliabilities were comparable to those obtained in the presented study (see Cipora, van Dijck, et al, 2018, for a comparison). Recently, Cipora and Wood (2017) showed that the power to detect the SNARC as well as to find between group differences in the effect largely depends on the number of repetitions of each number in a block. Increasing the number of trials leads to higher power.…”
Section: Reliabilitymentioning
confidence: 99%